Holocaust graphic narratives : generation, trauma, and memory - Aarons, Victoria 1952- (Rutgers University Press, 2020)
"Holocaust Graphic Narratives examines Holocaust graphic novels and memoirs, analyzing the genre as one that enables intergenerational transmission of trauma and memory. Here, the graphic novel becomes a medium uniquely positioned to create a sense of felt immediacy, urgency, and authenticity at the intersection of history and the imagination"--